If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 29 + -1(x + 6) = 9x + -7 Reorder the terms: 29 + -1(6 + x) = 9x + -7 29 + (6 * -1 + x * -1) = 9x + -7 29 + (-6 + -1x) = 9x + -7 Combine like terms: 29 + -6 = 23 23 + -1x = 9x + -7 Reorder the terms: 23 + -1x = -7 + 9x Solving 23 + -1x = -7 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. 23 + -1x + -9x = -7 + 9x + -9x Combine like terms: -1x + -9x = -10x 23 + -10x = -7 + 9x + -9x Combine like terms: 9x + -9x = 0 23 + -10x = -7 + 0 23 + -10x = -7 Add '-23' to each side of the equation. 23 + -23 + -10x = -7 + -23 Combine like terms: 23 + -23 = 0 0 + -10x = -7 + -23 -10x = -7 + -23 Combine like terms: -7 + -23 = -30 -10x = -30 Divide each side by '-10'. x = 3 Simplifying x = 3
| 3r+8=20 | | 4*(x+2)=18 | | -17=p+3-3p | | 9y-12-4y+9=0 | | 12+9x-6x-19= | | c(c-5)=14 | | 8y-14-4y+9=0 | | 5.3=z-2.7 | | 4x=x-25 | | 6(w+1)=2(w+5) | | 4-3x-10=-18 | | -6(1-5x)+x=2x-35 | | a^2+30a-4000=0 | | 11/x+5/x=4 | | 6(5x-5)+3(16-3x)-4(5x+1)=-1 | | 2(3x-5)-8=8 | | 11d+5f-21d+5-8= | | -2(1-7r)=-86 | | 10(-6+x)=-10 | | 1/2(20)(28) | | 5x+25=5x+9 | | 2(3m-5)=-28 | | 0.3x+1.7=1.7 | | x+0.2x=7.2 | | 3x+7=23-2x | | 0.25x=2 | | 3mn+4m-2mn= | | 8r-5r+4=6r-r | | 50+40=200+4x | | 11q+5p-9q+7p= | | -(5y+4)-(-4y-6)=-2 | | 4y-30+2y=18 |